The Arctic window: a view to Greenland’s foreign policy - Hviid, Alexander Niels-Jacob (Politica, 2022)
In both the Home Rule Act as well as the Self-Government Act, it was made clear that Greenland had and has a certain legal leeway to conduct its own foreign policy. However, the exact extent of this leeway has always been unclear. This legal ambiguity played out in practice in the case of the “Arctic Window” from 1999. Then as now, Copenhagen and Nuuk had divergent interpretations of Greenland’s leeway to conduct its own foreign policy – this divergence was not communicated openly but rather swept under the rug. The fundamental legal ambiguity has been perpetuated in the Self-Government Act in force today. The dynamics explored in this article thus continue to hamper Danish-Greenlandic relations. This becomes increasingly problematic as the geopolitical competition in the Arctic draws in growing numbers of international actors, which the Danish Kingdom must be able to handle.